Assessment of Knowledge, Attitude, and Practice Regarding Diabetic Retinopathy in an Urban Population in Northeast China - Qi, Jin-Yan; Zhai, Gang; Wang, Yu; Liang, Yuan-Bo; Li, Dong; Wen, Liang; Zang, Dong-Xiao; Feng, Ke-Mi; Zang, Bo; Xie, Cong (Frontiers in Public Health, 2022)
Objective: This study aimed to assess the knowledge, attitude, and practice (KAP) of diabetic subjects with diabetic retinopathy (DR) and those without DR (NDR) in an urban community in northeast China, as well as their risk factors in subjects with DR and NDR. Methods: A community-based survey involving 1,662 subjects was conducted in Fushun, China, between July 2012 and May 2013. The subjects included diabetics with DR (n = 783) and those NDR (n = 879), and questionnaires were completed to collect information about their sociodemographic and healthcare characteristics. A Chi-square test and multiple logistic analyses were performed to analyze the data. Results: Among the DR group, 21.88% had a good knowledge of DR, 94.15% had a positive attitude, and 68.07% followed good practice, whereas 20.98% of the NDR group had a good knowledge of DR, 94.18% had a positive attitude, and 66.92% followed good practice. There was no significant difference in the KAP of the two groups of subjects. In the NDR group, a good level of knowledge was associated with a high-level of education (OR = 0.1, 0.2; p < 0.05), a good attitude was associated with retirement (OR = 0.2; p < 0.05), and good practice was associated with being female, having a high-level of education, and the type of treatment (OR = 0.5, 0.4, 2.3, 3.1; p < 0.05). In the DR group, good practice was associated with older age and retirement (OR = 0.6, 0.4; p < 0.05). Conclusions: There was no significant difference between the DR and NDR subjects in the overall levels of KAP, but both groups showed a poor level of knowledge. Age, gender, education, occupation, and type of treatment were the main factors associated with the KAP scores, more risk factors in the NDR group than in the DR group. There is an urgent need for coordinated educational campaigns with a prioritized focus on the northeast region of China, especially NDR group.